Risk management analysis and investment strategy on forex online trading - Hartono, Hartono; Nersiwad, Nersiwad; Muslimin, Mohammad; Asj'ari, Fachrudy; Martins, Moses (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The purpose of this study is to analyze risk management and investment strategies in Forex Online Trading. The method used in this study is a qualitative method with a descriptive description. Data collection techniques using qualitative analysis. The results show that risk management in Forex Online Trading can be reviewed through risks that can be reached by traders, as well as market risks that cannot be reached by traders. The first risk can be reviewed through total equity risk and trading position risk, while market risk can be reviewed through portfolio diversification, understanding price changes and volatility, and understanding leverage and margin. An investment strategy in Forex Online Trading can be considered through four types of methods, namely the Martingale trading strategy, the Trading by News strategy, and the Pending Order strategy.